1996
DOI: 10.1038/nm0496-467
|View full text |Cite
|
Sign up to set email alerts
|

Aminoglycoside antibiotics restore CFTR function by overcoming premature stop mutations

Abstract: Cystic fibrosis (CF) is caused by mutations in the gene encoding the CF transmembrane conductance regulator (CFTR). A single recessive mutation, the deletion of phenylalanine 508 (deltaF508), causes severe CF and resides on 70% of mutant chromosomes. Severe CF is also caused by premature stop mutations, which are found on 5% of CF chromosomes. Here we report that two common, disease-associated stop mutations can be suppressed by treating cells with low doses of the aminoglycoside antibiotic G-418. Aminoglycosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
273
0
5

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 442 publications
(289 citation statements)
references
References 18 publications
6
273
0
5
Order By: Relevance
“…First, a precise quantification of readthrough was obtained using reporter systems, either by transfection of cultured cells or through expression of synthetic RNAs in rabbit reticulocyte lysates. 5,15 Secondly, the re-expression of a mutated gene after gentamicin treatment has been assessed in animal models, such as Mdx mdx or CFTR mutant mice. 6,8 However, the correlation between readthrough levels obtained in vitro or ex vivo and the re-expression observed in vivo remained uncertain, since several processes might modulate the primary molecular effect of the antibiotic on readthrough, in particular mRNA stabilization and protein accumulation.…”
Section: Readthrough In Vivomentioning
confidence: 99%
See 2 more Smart Citations
“…First, a precise quantification of readthrough was obtained using reporter systems, either by transfection of cultured cells or through expression of synthetic RNAs in rabbit reticulocyte lysates. 5,15 Secondly, the re-expression of a mutated gene after gentamicin treatment has been assessed in animal models, such as Mdx mdx or CFTR mutant mice. 6,8 However, the correlation between readthrough levels obtained in vitro or ex vivo and the re-expression observed in vivo remained uncertain, since several processes might modulate the primary molecular effect of the antibiotic on readthrough, in particular mRNA stabilization and protein accumulation.…”
Section: Readthrough In Vivomentioning
confidence: 99%
“…Bedwell and co-workers 4,5 have also shown that G-418 and gentamicin can restore the expression of the cystic fibrosis transmembrane conductance regulator (CFTR) in a bronchial cell line with a nonsense mutation in the CFTR gene. Similarly, a Hurler syndrome fibroblast cell line heterozygous for a stop mutation showed a significant increase in alpha-L-iduronidase when cultured in the presence of gentamicin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dietary supplementation of sapropterin, a synthetic form of BH 4 , the cofactor of PAH, is efficacious in a subset of PAH mutations in lowering blood Phe levels (Kure et al 1999;Bernegger and Blau 2002). More recently, a novel set of compounds have been developed specifically targeting nonsense mutations and in vitro studies have shown that these compounds may be of therapeutic benefit in PKU patients carrying nonsense mutations (Howard et al 1996;Barton-Davis et al 1999;Welch et al 2007;Du et al 2009;Nudelman et al 2010;Ho et al 2013). Mutation screening would identify those patients for whom these approaches, including other mutation-specific therapies such as anti-aggregation compounds for p.G46S (Leandro et al 2011), may be applicable.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro and in vivo studies have suggested that this strategy may be relevant for human diseases. Suppression of a nonsense mutation in the cystic fibrosis transmembrane conductance regulator gene by growth in gentamicin increased cystic fibrosis transmembrane conductance regulator expression by 10 to 20 % compared to control cells and restored cAMP-activated chloride transport [149,150]. In a mouse model of Duchenne muscular dystrophy, gentamicin was used to disrupt translational fidelity to phenotypically correct a nonsense mutation [151].…”
Section: Models Of Dravet Syndromementioning
confidence: 99%